Exercise Capacity in Patients with the Total Artificial Heart. Issue 1 (January 2019) - Canada, Justin M.; Evans, Ronald K.; Abbate, Antonio; Arena, Ross; Tang, Daniel G.; Kasirajan, Vigneshwar; Shah, Keyur B.
Abstract : There is a dearth of information regarding the functional abilities of patients with the total artificial heart (TAH). Increased utilization of the TAH and patient discharge to home with the portable unit necessitates a shift in focus to quality of life, which includes quantifying and ultimately optimizing functional capacity. To date, only single-patient case studies have described the exercise response of the TAH patient. Fourteen patients with the TAH underwent cardiopulmonary exercise testing with concurrent analysis of TAH device function. All device settings remained fixed during testing. Peak oxygen consumption (VO2 ; 0.872 L/min [interquartile range (IQR) = 0.828–1.100 L/min]), percent predicted peak VO2 (36% [IQR = 32–42%]), and ventilatory anaerobic threshold (0.695 L/min [IQR = 0.542–0.845 L/min]) were markedly reduced in the TAH compared with predicted normal values. Determinants of VO2 using device-generated hemodynamics revealed a blunted cardiac output (+9% increase) and exaggerated oxygen extraction with exercise. Peak VO2 strongly correlated with resting (R = +0.548, p = 0.045), ventilatory anaerobic threshold (R = +0.780, p = 0.001), and peak exercise cardiac output (R = +0.672, p = 0.008). Patients with the TAH have significantly impaired exercise performance. The limitations to cardiopulmonary exercise testing performance appear to be related to limited ability of the pump to modulate output for activity and reduced oxygen carrying capacity.